Enhanced production of terrein in marine-derived Aspergillus terreus by refactoring both global and pathway-specific transcription factors - Guangshan Yao; Xinfeng Bai; Bingxin Zhang; Lu Wang; Songbiao Chen; Zonghua Wang (Microbial Cell Factories, 2022)
Abstract Background Terrein, a major secondary metabolite from Aspergillus terreus, shows great potentials in biomedical and agricultural applications. However, the low fermentation yield of terrein in wild A. terreus strains limits its industrial applications. Results Here, we constructed a cell factory based on the marine-derived A. terreus RA2905, allowing for overproducing terrein by using starch as the sole carbon source. Firstly, the pathway-specific transcription factor TerR was over-expressed under the control of a constitutive gpdA promoter of A. nidulans, resulting in 5 to 16 folds up-regulation in terR transcripts compared to WT. As expected, the titer of terrein was improved in the two tested terR OE mutants when compared to WT. Secondly, the global regulator gene stuA, which was demonstrated to suppress the terrein synthesis in our analysis, was deleted, leading to greatly enhanced production of terrein. In addition, LS-MS/MS analysis showed that deletion of StuA cause decreased synthesis of the major byproduct butyrolactones. To achieve an optimal strain, we further refactored the genetic circuit by combining deletion of stuA and overexpression of terR, a higher terrein yield was achieved with a lower background of byproducts in double mutants. In addition, it was also found that loss of StuA (both ΔstuA and ΔstuA::OEterR) resulted in aconidial morphologies, but a slightly faster growth rate than that of WT. Conclusion Our results demonstrated that refactoring both global and pathway-specific transcription factors (StuA and TerR) provides a high-efficient strategy to enhance terrein production, which could be adopted for large-scale production of terrein or other secondary metabolites in marine-derived filamentous fungi.